The literary creation according to Lacan, knots and strings: a reflection on the sinthome - Asensi Pérez, Manuel (2023)
This article aims to examine Lacan’s thought on literary creation. With this aim in mind, we take as a point of reference Seminar 23, in which he deals with what Lacan calls the sinthome, a word in which he injects classical Greek into French, following the model of the Irish writer James Joyce, the object of analysis in the seminar. At the same time, some considerations are made with respect to some aspects of the sinthome that studies have interpreted in different ways, to end up proposing a new formula for this concept: sinthome 2. This comes from the fact that, at a certain point in this seminar, Lacan asserts that in the oedipal process the father is a sinthome. If this is so, it follows that literary writing as a sinthome can only be a second sinthome in relation to the first.